Maternal And Fetal Outcomes Of Unbooked Cases Presenting In Obstetrical Emergency Of Public Sector Tertiary Hospitals Of Rawalpindi. - Nimra Mubeen; Rameen Khalid; Arooj Bibi; Amarah Rashid; Dr.Mariya; Dr.Mehwish Riaz (Students' Supplement of Journal of Rawalpindi Medical College, 2025)
INRODUCTION: Obstetric emergencies significantly affect both the mother and fetus, leading to considerable maternal and perinatal morbidity and mortality. Reducing maternal and newborn mortality and morbidity is a top priority for the global healthcare system.OBJECTIVES: The objectives of this study is to assess the maternal and fetal outcomes of un-booked patients presenting in emergency of Tertiary Care Hospital. METHODOLOGY: The self-administered questionnaire was used to obtain data and was cleaned and analyzed using excel and SPSS version 27. Descriptive statistics were found for demographic variables and maternal and fetal outcomes. RESULTS: Out of 200 participants ,maternal outcomes were uneventful in 144(72%) , anemia 25(12.5%), fever 14 (7.0%) and post-partum hemorrhage in 15(7.5%) being the most common pathological outcomes. Only a few had cerebrovascular accidents 4 (2%), wound sepsis 3(1.5%), maternal genital injuries 2 (1%) and acute renal failure 1(0.5%). No incidence of coma or death was found. Fetal outcomes were: 152(76%) of the fetus were live at birth.35(17.5%) were NICU admissions. CONCLUSIONS: The study's findings emphasize the outcomes linked to un-booked patients in obstetrical emergencies. These insights can influence health policies aimed at enhancing maternal and fetal outcomes. By identifying gaps, targeted interventions, improved emergency preparedness, and awareness campaigns can be initiated to reduce morbidity and mortality rates, ultimately promoting better health for mothers and newborns in tertiary care settings. KEYWORDS: Obstetrical Emergencies, Un-booked patients, Maternal Outcomes, Fetal Outcomes